“Unsung” business strategy: Exploring crowd sourcing practices among Malaysian SMEs - Mansor, Mohd Fitri; Abdul Halim, Hasliza; Ahmad, Noor Hazlina; Abu, Noor Hidayah (School of Technology Management and Logistics (STML), 2019)
The emerging of Internet of Things (IoTs) and changing global environment lead the demand for every organization to change and sustain their business. Due to this forces, the organization has no choice and forced to adapt with new Information and Communication Technology (ICT) or Technology Web 2.0 such as social media in order to strengthen their business strategy and for the business survival. Based on previous literature reviews, numerous strategies adopted by the organization as the mechanism to improve and sustain in their business performance. Amongst the business strategies are Lean Manufacturing (AlManei, Salonitis & Zu, 2017); Total Quality Management (TQM) (Sahoo & Yadav, 2018); Cloud Computing (Hassan, 2017); New Product Development (Abu, Mansor & Nasir, 2017); Human Capital (Muda & Che Abdul Rahman, 2016); Kaizen (Maarof & Mahmud, 2016) and many more. Nevertheless, the recent “unsung” business strategy or a new business strategy not being realize among the business owners is known as crowd sourcing practices. The phenomenon of crowd sourcing describes a new form of outsourcing tasks or value creation activities and function by tapping from external parties such as an individual, group, freelancer or any undefined group of people or crowds that are possessed heterogeneous of backgrounds, skill and knowledge, intelligence ideas to perform the organization tasks (Durward & Blohm, 2017). Crowd sourcing practices was introduced by Jeff Howe (2006) in the Wired Magazine articles. It refers to new phenomenon and as open business model in order to obtain diverse web-based solution from unknown individual or group of people to earn money by completing the projects or tasks (Howe, 2006; Liu et al., 2016).